Answer:
y = [tex]\frac{1}{3}[/tex] x
Step-by-step explanation:
Compare the values of y with the values of x for each ordered pair
x y
3 1 → y = 3 ÷ 3
6 2 → y = 6 ÷ 3
9 3 → y = 9 ÷ 3 = 3
12 4 → y = 12 ÷ 3 = 4
15 5 → y = 15 ÷ 3 = 5
The y value in each case is the x value divided by 3
Hence rule is
y = [tex]\frac{1}{3}[/tex] x
NEED HELP ASAP PLEASE
Find the ratio of the known sides and calculate X.
1. The smaller triangle is half the size of the lager one:
6/12 = 1/2
10/12 = 1/2
This means x is half the length of 16
x = 16/2 = 8
2. 18/30 = 3/5
9/15 = 3/5
This means x is 3/5 of 25
x = 25 * 3/5 = 15
3. 32/24 = 1 1/3
16 /12 = 1 1/3
X is 1 1/3 times the length of 21
x = 21 x 1 1/3
x = 28
4. 12/15 = 4/5
20/25 = 4/5
x is 4/5 the length of 40
x = 40 * 4/5
x = 32
Jeri is 3 years younger than Laura, whose age is x. How old is Jeri? x - 3 yrs old x + 3 yrs old 3x yrs old
Answer:
3x yrs old
Step-by-step explanation:
what is 6/7divided into 3/14 plz helppp meh
Answer:
4
Step-by-step explanation:
6/7 divided by 3/14 is 4.
Find common denominators.
6/7 would be changed into 12/14.
3/14 would stay the same because its denominator is already 14.
12/3 = 4
Therefore, 6/7 divided by 3/14 is 4.
Answer:
The answer is 4
Step number one use the butterfly method:
6 14
-- ×---- =84/21
7 3
Step 2: Divide since it's improper
84÷21=4
4 21
-- × --- =4
1 21
(3a-2b)(3a+3b) so this is foil but i always get messed up on it does anyone now how to do it
Answer:
9a^2 + 3ab - 6b^2
Step-by-step explanation:
(3a-2b)(3a+3b)
First term of each grouping is 3a and 3a.
Multiply those you get 9a^2.
Outer term of each grouping is 3a and 3b.
Multiply those you get 9ab.
Inner term of each grouping is -2b and 3a.
Multiply those you get -6ab.
Last term of each grouping is -2b and 3b.
Multiply those you get -6b^2.
Add up all your products from above.
9a^2+9ab+-6ab+-6b^2
There are like terms here. The 9ab+-6ab which is 3ab.
So you can write your expression now as:
9a^2 + 3ab +-6b^2
9a^2 + 3ab - 6b^2
Step-by-step explanation:
[tex]\text{Use FOIL}\ (a+b)(c+d)=ac+ad+bc+bd:\\\\(3a-2b)(3a+3b)\\\\=(3a)(3a)+(3a)(3b)+(-2b)(3a)+(-2b)(3b)\\\\=9a^2+9ab-6ab-6b^2\qquad\text{combine like terms}\\\\=9a^2+3ab-6b^2[/tex]
Jamin wants to paint a wall in his bedroom. Not only does he need to buy paint, but he also needs to buy tape to tape off all sides of the wall and the window. How many feet of painter's tape will Jamin need to buy (assume no overlap)? [Note: The wall and window are both rectangular.]
17.5 ft
35 ft
28 ft
21 ft
The perimeter of the walls is 6 + 6 + 8 + 8 = 28 feet.
The perimeter of the window is 2 + 2 + 1.5 + 1.5 = 7 feet.
Total = 28 + 7 = 35 feet of tape.
I would say B.35 is the answer.
Find the sixth term of the
geometric sequence, given the
first term and common ratio.
a1=5 and r=3/2
Answer:
[tex]\frac{1215}{32}[/tex]
Step-by-step explanation:
The n th term of a geometric sequence is
[tex]a_{n}[/tex] = a₁ [tex](r)^{n-1}[/tex], hence
[tex]a_{6}[/tex] = 5 × [tex](\frac{3}{2 )} ^{5}[/tex] = 5 × [tex]\frac{243}{32}[/tex] = [tex]\frac{1215}{32}[/tex]
The sixth term of the geometric sequence is 1215/32 given that the first term a₁=5 and common ratio r=3/2. This can be obtained by using formula for nth term of the geometric sequence.
What is a geometric sequence?
Sequence is s collection of objects in a particular order and repetitions are allowed.
Geometric Sequence:
a, ar, ar¹, ..., arⁿ⁻¹ is a geometric sequence, where a is the first term, r is the common ratio and arⁿ⁻¹ is the nth term.
Calculate the sixth term:From the definition, nth term of a geometric sequence is arⁿ⁻¹.
Given that, a₁=5 and r=3/2
To find sixth term, put n=6 ⇒ arⁿ⁻¹=(5)(3/2)⁶⁻¹
=(5)(3/2)⁵
=5(3⁵/2⁵)
=5×(243/32)
=1215/32
Hence the sixth term of the geometric sequence is 1215/32 given that the first term a₁=5 and common ratio r=3/2.
Learn more about geometric sequence here:
brainly.com/question/2959141
#SPJ2
what is the approximate area of the circle shown below? 16 cm
Answer:
201.143 (approx.) cm²
area of circle = (pi)x(radius)^2
= 22/7 x (8)^2
=22/7 x 64
= 1408/7
= 201.142857143
= 201.143 cm^2 (approx.)
Answer:
the approximate area of circle is 201 cm²
D is the correct option.
Step-by-step explanation:
From, the given figure, the diameter of the circle is 16 cm.
The radius is half of the diameter.
Hence, the radius of circle is 16/2 = 8 cm
The area of a circle is given by
[tex]A=\pi r^2[/tex]
Substituting the value of r and π
[tex]A=3.14(8)^2\\\\A=200.96\\\\A\approx201[/tex]
Therefore, the approximate area of circle is 201 cm²
D is the correct option.
In the table, the parts of strawberry concentrate and the parts of water to prepare a strawberry drink are given. There is a proportional relationship between these two quantities. Find the value of x.
Parts of Water 3 9 36
Parts of Concentrate 1 3 x
Answer:
12
Step-by-step explanation:
[tex]\frac{Parts of Water}{Parts of Concentrate} =3[/tex]
3/1=3
9/3=3
36/12=3
Choose the equation that represents the line that passes through the point (6,-3,) and has a slope of 1/2
Answer:
[tex]y=\frac{1}{2}x-6[/tex]
Step-by-step explanation:
The general equation of a line: [tex]y = ax+b[/tex]
In our case a is given
[tex]a=\frac{1}{2}[/tex]
Now we plug in for a and we get:
[tex]y=\frac{1}{2}*x+b[/tex]
Now we plug in our coordinates into this equation and we solve for b
[tex]-3=\frac{1}{2}*6+b\\b = -6[/tex]
So the equation of the line is [tex]y=\frac{1}{2}x-6[/tex]
Answer:
[tex]y=\frac{1}{2}x-6[/tex]
Step-by-step explanation:
Since the Inclination of the line was already given to us. Let us use Inclination of line formula:
[tex]m=\frac{y-y_0}{x-x_0}[/tex]
Plugging it in those values then we have the equation of the line:
[tex]\frac{1}{2}=\frac{y+3}{x-6}[/tex]
Rewriting, multiplying both sides
2y+6=x-6
2y=x-12 Rearranging
[tex]y=\frac{1}{2}x-6[/tex]
Given the functions, F (x)=√(2x-5) and g(x) = 3x 2 + 2, perform the indicated operation. f(g(x))
Answer:
[tex]f(g(x)) =\sqrt{6x^2-1}[/tex]
Step-by-step explanation:
Given
f(x) = √2x-5
and
g(x) = 3x^2+2
We have to find the composition of both function
f(g(x)) means that we have to put function g in place of x in function f.
[tex]f(g(x))= \sqrt{2*g(x)-5}\\ =\sqrt{2(3x^2+2)-5}\\=\sqrt{6x^2+4-5}\\=\sqrt{6x^2-1}[/tex]
..
The composite function f(g(x)) is given by f(g(x)) = √(6x^2 - 1).
To find the composite function f(g(x)), you need to substitute the expression for g(x) into the function f(x). Here's how you can do it step by step:
Start with the function g(x):
g(x) = 3x^2 + 2
Now, substitute this expression into the function f(x):
f(g(x)) = √(2(3x^2 + 2) - 5)
Simplify the expression inside the square root:
f(g(x)) = √(6x^2 + 4 - 5)
Further simplify the expression inside the square root:
f(g(x)) = √(6x^2 - 1)
So, the composite function f(g(x)) is given by:
f(g(x)) = √(6x^2 - 1)
for such more question on composite function
https://brainly.com/question/10687170
#SPJ3
You have $60. The jacket you want costs $25.50 and 7% tax. what is the top tag price (excludes sales tax) left to also buy a pair of shorts?
the assumption being, that there's a 7% sales tax on any item in the store.
so if you buy the jacket, you pay 25.5 plust 7% of 25.5.
and if you buy the shoes for price say "s", then you pay "s" plus 7% of "s".
whatever those two amounts are, they must be $60, because that's all you have in your pocket anyway.
[tex]\bf \begin{array}{|c|ll} \cline{1-1} \textit{a\% of b}\\ \cline{1-1} \\ \left( \cfrac{a}{100} \right)\cdot b \\\\ \cline{1-1} \end{array}~\hspace{5em}\stackrel{\textit{7\% of 25.5}}{\left( \cfrac{7}{100} \right)25.5}\implies 0.07(25.5)~\hfill \stackrel{\textit{7\% of "s"}}{\left( \cfrac{7}{100} \right)s}\implies 0.07s \\\\[-0.35em] ~\dotfill[/tex]
[tex]\bf \stackrel{\textit{jacket}}{25.5}+\stackrel{\textit{jacket's tax}}{0.07(25.5)}+\stackrel{\textit{shoes}}{s}+\stackrel{\textit{shoe's tax}}{0.07s}~~=~~\stackrel{\textit{in your pocket}}{60} \\\\\\ 25.5+1.785+s+0.07s=60\implies 27.285+1.07s=60 \\\\\\ 1.07s=60-27.285\implies 1.07s=32.715\implies s=\cfrac{32.715}{1.07}\implies s\approx 30.57[/tex]
what is the coefficient of x^3 in the expansion of (2x-3)^5?
A) -5
B) 10
C) -120
D) -360
E) 720
Answer:
309
Step-by-step explanation:
(2x-)^5
step 1
1 5 10 10 5 1
step 2
1(2x¹-3^0) 5(2x²-3^5) 10(2x³-3^4)
10(2x^4-3³) 5(2x^5-3²)
1(2x^0-3¹)
step 3
(2x) (10x²-243) (20x³-81) (20x^4-27)
(10x^5-9) (2-3)
step 4
2 -243-61-7 +1 -1=309
The coefficient of [tex]x^3[/tex] in the expansion of [tex](2x-3)^5[/tex] is 720
The correct answer is an option (E)
What is coefficient?"It refers to a number or quantity placed with a variable."
What is variable?"The alphabetic character that expresses a numerical value."
What is an expression?"It is a mathematical expression which consists of numbers, variables and mathematical operations."
Formula for [tex](a-b)^3[/tex]" [tex](a-b)^3=a^3-3a^2b+3ab^2- b^3[/tex] "
Formula for [tex](a-b)^2[/tex]" [tex](a-b)^2=a^2-2ab+b^2[/tex] "
For given question,
We have been given an expression [tex](2x-3)^5[/tex]
We need to expand given expression.
[tex](2x-3)^5\\\\= (2x-3)^3\times (2x-3)^2\\\\=[(2x)^3-3(2x)^23+3(2x)(3)^2- 3^3]\times ((2x)^2-2(2x)(3)+3^2)\\\\=[8x^3-36x^2+54x-27]\times [4x^2-12x+9]\\\\=-243+810x-1080x^2 +720x^3-240x^4+32x^5\\\\=32x^5-240x^4+720x^3-1080x^2+810x-243[/tex]
Therefore, the coefficient of [tex]x^3[/tex] in the expansion of [tex](2x-3)^5[/tex] is 720
The correct answer is an option (E)
Learn more about the coefficient here:
https://brainly.com/question/13431100
#SPJ2
What is the volume of the regular pyramid bellow?
Answer:
128 units^3
Step-by-step explanation:
[tex]v = \frac{b \times b \times h}{3} = \\ = \frac{8 \times 8 \times 6}{3} = \\ = 128 \: {units}^{3} [/tex]
Step-by-step explanation:
base areas x height / 3
a^2 . h / 3
8^2 . 6 / 3
= 128 units^3
iyi ödevler
have a good lesson
HELP PLEASE!
simplify
(2x^3y)^3 / (4xy^2)^2(xy^3)
Answer:
[tex]\large\boxed{\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}=\dfrac{x^6}{2y^4}}[/tex]
Step-by-step explanation:
[tex]\dfrac{(2x^3y)^3}{(4xy^2)^2(xy^3)}\qquad\text{use}\ (ab)^n\ \text{and}\ (a^n)^m=a^{nm}\\\\=\dfrac{2^3(x^3)^3y^3}{4^2x^2(y^2)^2xy^3}\qquad\text{cancel}\ y^3\\\\=\dfrac{8x^{(3)(3)}y^3\!\!\!\!\!\diagup}{16x^2y^{(2)(2)}xy^3\!\!\!\!\!\diagup}\\\\=\dfrac{8\!\!\!\!\diagup^1x^9}{16\!\!\!\!\!\diagup_2x^2y^4x}\qquad\text{use}\ a^na^m=a^{n+m}\\\\=\dfrac{x^9}{2x^{2+1}y^4}\\\\=\dfrac{x^9}{2x^3y^4}\qquad\text{use}\ \dfrac{a^n}{a^m}=a^{n-m}\\\\=\dfrac{x^{9-3}}{2y^4}\\\\=\dfrac{x^6}{2y^4}[/tex]
Which of these is a trinomial?
A. 2x-7
B. 2x2 - 7/3 + 14
c. 2y2 + 7y
D. 5xy
Answer:
the answer is D
Step-by-step explanation:
a is not it has a negative
a b is not it has an equation in it
so that leaves it to see and d c does not work
because it has to have two variables per one number
Which of the following is equivalent to
Answer:
[tex]x^{4}[/tex]
Step-by-step explanation:
[tex]\frac{x^{5}y^{2} }{xy^{2} }[/tex]
= [tex]x^{4}[/tex]
Question 1:
For this case we have the following expression:
[tex]\frac {x ^ 5y ^ 2} {xy ^ 2}[/tex]
We eliminate similar terms in the numerator and denominator:
[tex]\frac {x ^ 5} {x}[/tex]
By definition of division of powers of the same base we have to place the same base and subtract the exponents:
[tex]\frac {x ^ 5} {x} = x ^ {5-1} = x ^ 4[/tex]
ANswer:
Option D
Question 2:
For this case we must indicate which expression is not equal to 125.
We tested option A:
[tex]5 (\frac {5 ^ 3} {\frac {2} {5}}) ^ 2 =[/tex]
Simplifying we have:
[tex]5 (\frac {5 ^ 3 * 5} {2}) ^ 2 =\\5 (\frac {5 ^ 8} {4}) =\\\frac {5 ^ 9} {4}[/tex]
The expression is not equal to 125.
Answer:
option A
A light bulb company produces a constant number of new light bulbs in their factory each week, and stores them in a warehouse where old light bulbs from the previous year are also stored. After 3 weeks, they have 15,000 bulbs in the warehouse. After 7 weeks, they have 65,000 bulbs.
What is the equation in point-slope formula?
Answer:
y - 15000 = 12500(x-3)
What are the solutions of the equation x^4+ 95x^2-500=0? Use factoring to solve
Answer:
x^4+100x^2-5x^2-500=0
x^2(x^2+100)-5(x^2+100)=0
(x^2+100)(x^2-5)=0
from first expression
x^2+100=0
x^2=-100
x= root under -100
Therefore x=-10
from next expression
x^2-5=0
x^2=5
Or x=2.23
Step-by-step explanation:
Answer:
x = ± sqrt(5)
x = ±10i
Step-by-step explanation:
x^4+ 95x^2-500=0
What two numbers multiply to -500 and add to 95
-5 * 100 = -500
-5 +100 = 95
(x^2 - 5) (x^2 + 100) = 0
Using the zero product property
x^2 -5 =0 x^2 +100 =0
x^2 -5+5 =0 x^2 +100-100 = 0-100
x^2 =5 x^2 = -100
Take the square root of each side
x = ± sqrt(5) x = imaginary numbers
x = ±10i
True or false? An angle whose vertex is at the center of the circle is a central angle of that circle.
This statement would be true: if the vertex of an angle is at the center of the circle, then it would be the central angle.
Question 1
1 pts
Maureen worked 48 hours last week. Her hourly rate is $8.00. What was her salary, not
including overtime pay?
• 384.00
230.00
320.00
480.00
Answer:
$384.00
Step-by-step explanation:
Since $8..0 is 1 hour, just multiply 48 x 8! Hope this helps!
Answer:
320
Step-by-step explanation:
The reason that you 48* 8 is because the 48 has overtime included in it so you would only 40*8.
Which equation is used to help form the combined gas law?
Need help ASAP !
If pressure is constant
then PV= nRT
is equivalent to V= ( nR/P) T
V= kT ( where k is constant nR/P)
As V is directly proportional to T
So V1/T1 = V2/T2
Answer:
The correct answer
Step-by-step explanation:
Joseph claims that a scatterplot in which the y-values increase as the x-values increase must have a linear association. Amy claims that the scatterplot could have a nonlinear association. Which statement about their claims is true?
Joseph is correct because only a line will increase along the whole data set. The scatterplot will have a positive, linear association.
Joseph is correct because only a line will decrease along the whole data set. The scatterplot will have a negative, linear association.
Amy is correct because a nonlinear association could increase along the whole data set, while being steeper in some parts than others. The scatterplot could be linear or nonlinear.
Amy is correct because only a nonlinear association could increase along the whole data set. A line has the same slope at any point, but a curve can get steeper at different points.
Answer:
The answer is C
Step-by-step explanation:
Answer:
Amy is correct because a nonlinear association could increase along the whole data set, while being steeper in some parts than others. The scatterplot could be linear or nonlinear.
Step-by-step explanation:
Both linear and nonlinear associations could increase along the whole data set. That's why Joseph and the fourth option are incorrect.
janis jogs around a rectangular park that is 3/4 mi long and 1/4 mi wide. how far is it around the park?
Answer:
[tex]2\ miles[/tex]
Step-by-step explanation:
we know that
The distance around the park is equal to the perimeter of the rectangular park
The perimeter is equal to
[tex]P=2(L+W)[/tex]
we have
[tex]L=\frac{3}{4}\ mi[/tex]
[tex]W=\frac{1}{4}\ mi[/tex]
substitute the values
[tex]P=2(\frac{3}{4}+\frac{1}{4})[/tex]
[tex]P=2(\frac{4}{4})[/tex]
[tex]P=2\ mi[/tex]
Answer:
3 219⁄1000 km. [2 mi.]
Step-by-step explanation:
P = 2l + 2w
P = 2[¾] + 2[¼]
P = 1½ + ½
P = 2
I am joyous to assist you anytime.
What is the equation of the line that is parallel to the given line and passes through the point (-3, 2)?
4x + 3y = -6
Step-by-step explanation:
evaluate 3^-3 please explain
Answer:
D) 1/27
Step-by-step explanation:
The question is: 3^(-3).
Note that there is a negative sign in the number at the power place. This means that you must flip the number, and in this case, put it over 1. The rest is solved as usual:
3^-3 = 1/(3^3) = 1/(3 * 3 * 3) = 1/27
1/27, or D) is your answer.
~
3Q + 4T = 26. P=2T=3Q l. What is 6P?
The answer is 52 but I don’t understand how they got this answer
Step-by-step explanation and answer:
The given equations P=2T=3Q can be split up into
P=2T..................(1)
P=3Q................(2)
since they are all equal.
Rewrite the given equation
3Q + 4T = 26 .............(3)
as
3Q + 2(2T) = 26 ...........(4)
and substitute (1) and (2) into (4)
P + 2(P) = 26 .................(5)
Multiply (5) by two to get
6P = 2*26 = 52 ..............(6)
as given.
Answer:
see explanation
Step-by-step explanation:
Given P = 2T = 3Q, then
3Q + 4T = 26 can be expressed as
P + 2P = 26
3P = 26 ( multiply both sides by 2 )
6P = 52 ← as required
Why is the x intercept wrong?
what is the domain of this function?
Answer:
x ≥ 0
Step-by-step explanation:
The domain of the function is the inputs, or in this case, the x values.
The inputs are x greater than or equal to zero all the way to infinity.
Answer:
Step-by-step explanation:
The domain includes 0 and all real numbers greater than 0: x ≥ 0
Arnold has x amount of money in
his checking account. He spends
$12.36 for breakfast but has at least
$31.24 left in his account. How much
money did he have originally?
Answer:
43.60
Step-by-step explanation:
12.36+31.24
If X || Y and Y || Z then___
Answer:
X is parallel to Z
X || Z
Step-by-step explanation:
This is called the transitive property.
It says something like:
If f is related to g and g is related to h, then f is related to h.
The parallel relationship is transitive.
That is,
if X is parallel to Y and Y is parallel to Z, then X is parallel to Z.